The Literature Review of Pain and Sedation Scales for Neonatal and Pediatric Patients in a Preverbal Stage of Development - Felix, Felix; Ida Ayu Novita, Ida Ayu Novita (The Indonesian Journal of General Medicine, 2024)
Background: The assessment of pain and sedation in neonatal and pediatric patients who are preverbal presents a complex challenge, necessitating a thorough understanding of the available methodologies and their implications for clinical practice. The literature reveals a critical need for effective pain assessment tools tailored to the unique characteristics of this vulnerable population. Literature Review: The literature on pain and sedation assessment for neonatal and pediatric patients in a preverbal stage emphasizes the complexity and necessity of effective methodologies tailored to this vulnerable population. The studies reviewed highlight a critical need for reliable pain assessment tools that can accurately reflect the unique pain experiences of infants and young children. Conclusion: the reviewed literature underscores the urgent need for effective pain and sedation assessment tools specifically designed for neonatal and pediatric patients in a preverbal stage. The integration of technology, standardization of assessment protocols, and ongoing education for healthcare providers are critical to improving pain management outcomes in this vulnerable population.